Review of the Sri Lanka blue whale (Balaenoptera musculus) with observations on its distribution in the shipping lane - Randage, Sameera Madusanka; Alling, Abigail; Currier, Kitty; Heywood, Eleanor (J. Cetacean Res. Manage., 2023)
A population of blue whales is resident off the southern coast of Sri Lanka and has been observed year-round by the crew of a whalewatching vessel, Raja & the Whales, a few miles south of Mirissa Harbour. Over the course of three years (1 December 2009 to 30 November 2012), a total of 485 blue whale sightings were reported with an average of 4.56 individuals observed per sighting. This number does not represent the total number of individuals seen because repeat sightings were highly probable. Calves were observed during the northeast monsoon. Sightings were confined to an area of about 200 n.miles that is bisected by a heavily trafficked shipping lane. Much of this area is characterised by submarine canyons and sloping bathymetry, which contributes to monsoonal seasons of high productivity and upwelling suitable for feeding whales. While the numbers of injuries and fatalities due to ship strikes are not known, four dead blue whales were observed along the southern coast over the course of five months (1 January to 31 May 2014). It is of great urgency to understand the identity and size of this population, reduce ship strikes and address all issues threatening this population in order to arrive at possible mitigation measures for its protection.